0292 Sleep Spindle Characteristics and Their Association with Cerebrospinal Fluid Biomarkers of Alzheimer's Disease in Cognitively Normal Older Adults. (27th April 2018) - Varga, A W; Kam, K; Parekh, A; Sharma, R A; Castillo, B; Miller, M D; Bagchi, N; Rapoport, D M; Ayappa, I; Osorio, R S
Abstract: Introduction: Sleep has been identified as one of the factors that influence risk, manifestations, and possibly progression of Alzheimer's disease (AD). Although sleep spindles are associated with cognitive capacity, relationships between sleep spindles and amyloid beta and tau, hallmarks of AD, have not been evaluated in healthy normal elderly, prior to development of cognitive impairment. Methods: A cross-sectional study with CSF measures, 7 days of actigraphy, and in-lab nocturnal polysomnography was conducted on healthy cognitively normal elderly subjects to determine standard sleep measures and spindle characteristics. Fifty (50) subjects between the ages of 53 and 83 were screened for the absence of significant OSA. All subjects were non-depressed and had MMSE scores ≥ 26. CSF total-tau (T-tau), phosphorylated-tau 181 (P-tau181 ) and amyloid beta 42 (Aβ42 ) were measured using ELISA. Results: After controlling for age, sex, and ApoE genotype, spindle density during N2 sleep was negatively correlated with CSF T-tau (rho = -0.559, p < 0.001), CSF P-tau181 (rho = -0.446, p = 0.002) and CSF Aβ42 levels (rho = -0.326, p = 0.025). CSF T-tau was further negatively correlated with spindle duration (rho = -0.538, p < 0.001), spindle count (rho = -0.374, p = 0.007) and fast spindle density during N2 sleep (rho = -0.353, p = 0.012). Multiple regression analyses identified CSF T-tau as the strongest predictor for spindle density. Habitual sleep duration assessed by actigraphy, and WASO, sleep efficiency, and number of arousals during sleep measured during polysomnography were not correlated with these CSF measures in this cohort. Conclusion: The reduction in spindles during N2 sleep may represent an early dysfunction resulting from increasing tau in the brain, rendering it a potential novel biomarker for future neurodegeneration. Given their putative role in memory consolidation and neuroplasticity, sleep spindles represent a possible new target for therapeutic interventions in brain health during aging. While sleep duration and sleep fragmentation may influence later AD pathology, they do not appear to associate with early increases in CSF tau proteins. Support (If Any):